2009
DOI: 10.1152/ajpheart.00951.2008
|View full text |Cite
|
Sign up to set email alerts
|

Control of cardiac rate, contractility, and atrioventricular conduction by medullary raphé neurons in anesthetized rats

Abstract: The sympathetic actions of medullary raphé neurons on heart rate (HR), atrioventricular conduction, ventricular contractility, and rate of relaxation were examined in nine urethane-anesthetized (1-1.5 g/kg iv), artificially ventilated rats that had been adrenalectomized and given atropine methylnitrate (1 mg/kg iv). Mean arterial pressure (MAP), ECG, and left ventricular pressure were recorded. The peak rates of rise and fall in the first derivative of left ventricular (LV) pressure (dP/dtmax and dP/dtmin, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…It must be acknowledged that LVEDP is an indirect estimate of the left ventricular volume and could be used as an index of preload only if the ventricular compliance remains constant. Finally, as LVdP/dt in the rat heart is strongly affected by afterload (24, 42), we have controlled for this confounder by comparing ⌬(LVdP/dt)/ ⌬MAP ratio for DMH-induced responses to that provoked by administration of ␣-adrenergic agonist phenylephrine (30). As expected, phenylephrine provoked both pressor and contractile effect, but the magnitude of this afterload-induced contractile response was substantially smaller than the DMH-induced inotropic effect.…”
Section: Methodological Issuesmentioning
confidence: 94%
See 2 more Smart Citations
“…It must be acknowledged that LVEDP is an indirect estimate of the left ventricular volume and could be used as an index of preload only if the ventricular compliance remains constant. Finally, as LVdP/dt in the rat heart is strongly affected by afterload (24, 42), we have controlled for this confounder by comparing ⌬(LVdP/dt)/ ⌬MAP ratio for DMH-induced responses to that provoked by administration of ␣-adrenergic agonist phenylephrine (30). As expected, phenylephrine provoked both pressor and contractile effect, but the magnitude of this afterload-induced contractile response was substantially smaller than the DMH-induced inotropic effect.…”
Section: Methodological Issuesmentioning
confidence: 94%
“…In discussing this possibility, we would like to consider two medullary regions: the rostral ventrolateral medulla (RVLM) and the medullary raphe/parapyramidal area. In rats, chemical activation of either of these areas causes sympathetically mediated tachycardia and rise in cardiac contractility (3,4,6,30). Furthermore, anatomical tracing studies have demonstrated that both regions receive direct projections from the DMH (14,37) and that both regions, in turn, project to the heart, including to the ventricular myocardium (36,38,48).…”
Section: Neural Pathways Mediating Dmh-induced Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The midline raphé nuclei of the medulla oblongata, comprising predominantly 5-HT producing neurones, contain rather ill-defined sites shown to regulate cardiovascular function, as well as respiratory, thermoregulatory and (anti-) nociceptive functions (Blessing, 1997). Neurones in this region, including those of the parapyramidal area and rostroventromedial medulla have projections to the spinal IML and may function as sympathetic premotor neurones (Blessing, 1997;Salo et al, 2009;Goodchild and Moon, 2009). The midbrain dorsal raphé nuclei of primates and rodents strongly express ERb receptors, which have been shown to mediate changes in gene expression in 5-HT neurones, providing a substrate for oestrogen's effects on mood, arousal, pain perception and other neural functions (Bethea et al, 2002).…”
Section: Oestrogen Actions In Other Cns Nucleimentioning
confidence: 99%
“…This region has long been known to modulate sensorimotor processing important for nocifensor behaviors (Heinricher and Ingram, 2008), and has also been implicated in regulation of some sympathetic outflows, based on both anatomical and functional studies (Ter Horst et al, 1996; Blessing, 1997; Horiuchi et al, 2004; Nakamura et al, 2004; Kerman, 2008; Morrison et al, 2008; Salo et al, 2009). Positive and negative modulation of nociception and various aspects of autonomic regulation appear to be mediated by distinct RVM cell populations, but are likely recruited in a coordinated manner to orchestrate behavioral and physiological responses to internal and external threats (Lovick, 1997; Heinricher et al, 2009; Martenson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%